Use of food label information by urban consumers in India – a study among supermarket shoppers. Issue 9 (22nd August 2013) - Vemula, Sudershan R; Gavaravarapu, SubbaRao M; Mendu, Vishnu Vardhana Rao; Mathur, Pulkit; Avula, Laxmaiah
Abstract Objective To study consumer knowledge and use of food labels. Design A cross-sectional study employing both quantitative and qualitative methods. Intercept interviews were conducted with 1832 consumers at supermarket sites selected using a stratified random sampling procedure. This information was triangulated with twenty-one focus group discussions. Setting New Delhi and Hyderabad, two metro-cities from north and south India. Subjects Adolescent (10–19 years), adult (20–59 years) and elderly (≥60 years) consumers. Results While the national urban literacy rate is 84 %, about 99 % of the study participants were educated. About 45 % reported that they buy pre-packaged foods once weekly and about a fifth buy them every day. Taste, quality, convenience and ease of use are the main reasons for buying pre-packaged foods. Although 90 % of consumers across the age groups read food labels, the majority (81 %) looked only for the manufacturing date or expiry/best before date. Of those who read labels, only a third checked nutrition information and ingredients. Nutrient information on labels was not often read because most consumers either lacked nutrition knowledge or found the information too technical to understand. About 60 % read quality symbols. A positive association was found between education level and checking various aspects of food labels. Women and girls concerned about 'fat' and 'sugar' intake read the nutrition facts panel. Conclusions The intention of promoting healthy food choices through use of food labels is not being completely met. Since a majority of people found it difficult to comprehend nutrition information, there is a need to take up educational activities and/or introduce new forms of labelling.